Leveraging cell-specific differentially methylated regions to identify leukocyte infiltration in adipose tissue - Chu, Su H. (Genet Epidemiol, 2019)
Obesity is understood to be an inflammatory condition characterized in part by changes in resident immune cell populations in adipose tissue. However, much of this knowledge has been obtained through experimental animal models. Epigenetic mechanisms, such as DNA methylation may be useful tools for characterizing the changes in immune cell populations in human subjects. In this study, we introduce a simple and intuitive method for assessing cellular infiltration by blood into other heterogeneous, admixed tissues such as adipose tissue, and apply this approach in a large human cohort study. Associations between higher leukocyte infiltration, measured by evaluating a distance measure between the methylation signatures of leukocytes and adipose tissue, and increasing body mass index (BMI) or android fat mass (AFM) were identified and validated in independent replication samples for CD4 (p(BMI)=0.009, p(AFM)=0.020), monocytes (p(BMI)=0.001, p(AFM)=4.3×10(−4)) and dendritic cells (p(BMI)=0.571, p(AFM)=0.012). Patterns of depletion with increasing adiposity were observed for plasma B (p(BMI)=0.430, p(AFM)=0.004) and immature B (p(BMI)=0.022, p(AFM)=0.042) cells. CD4, dendritic, monocytes, immature B, and plasma B cells may be important agents in the inflammatory process. Finally, the method used to assess leukocyte infiltration in this study is straightforwardly extended to other cell types and tissues in which infiltration might be of interest.